CLIMATE RECONSTRUCTION FROM SUBSURFACE TEMPERATURES - Pollack H.N.; Huang S. (My University, 2000)
Temperature changes at the Earth's surface propagate downward into the subsurface and impart a thermal signature to the rocks. This signature can be measured in boreholes and then analyzed to reconstruct the surface temperature his-tory over the past several centuries. The ability to resolve surface temperature history from subsurface temperatures diminishes with time. Microclimatic effects associated with the topography and vegetation patterns at the site of a borehole, along with local anthropogenic perturbations associated with land use change, can obscure the regional climate change signal. Regional and global ensembles of boreholes reveal the broader patterns of temperature changes at the Earth's surface. The average surface tempera-ture of the continents has increased by about 1.0 K over the past 5 centuries; half of this increase has occurred in the twentieth century alone.